Green Integrated Marketing Communication Starbucks: Studi Kasus Pada Program Bring Your Own Tumblr - Dian Hutami Rahmawati; Farikha Rachmawati; Windri Saifuddin (JKOM, 2021)
Green Integrated Marketing Communication Starbucks: Studi Kasus Pada Program Bring Your Own Tumblr